Analisis Perpindahan Besar Akibat Gaya Non-Konservatif - Dolu, A.; Nasution, A.; Rivani, A.; Oka, G.M. (Civil Engineering Department, Tadulako University, 2022)
Structural applications based on large displacement analysis are widespread in various fields, such as the application of aircraft structures, membranes, cables, pipelines and risers. In this study, the author reviews the structural responses based on large displacement theory and non-conservative load models, assuming linear sections and materials. The parameters reviewed are the variation of the load factor and the variation of the slope angle of the load P at the end of the span. Solving non-linear differential equations with non-conservative force, using numerical integration method. The simulation results with the variation of the load factor with the angle of inclination, vertical and horizontal displacements are obtained, where the final orientation of the acting force corresponds to the deformation of the structure, and the maximum deformation occurs at a load angle of 90o, the deformation decreases for the angle orientation is getting smaller.